Development of PISA-like Activities using the Inquiry-based Learning Model and the Context of Religious Holidays during the Pandemic - Sisca Puspita Sepriliani; Zulkardi Zulkardi; Somakim Somakim (Jurnal Pendidikan Matematika, 2023)
This research aims to develop a PISA-type content quantity that uses the context of religious holidays during the pandemic that is valid, practical, and potentially affects mathematical literacy skills. This research uses development research with two stages: preliminary and formative evaluation. This research also uses Inquiry-Based Learning (IBL) model in the learning process. This study involved eighth-grade students aged 13-15 years of various abilities. Data collection and analysis techniques were documentation, walkthroughs, observation, interviews, and tests. The research was carried out offline and online (Zoom and WhatsApp Group (WAG)). In this study, sharing activities were produced as well as a PISA-type jumping task with content quantity characteristics in the context of religious holiday during the pandemic by the PISA 2022 framework where what needs to be considered are mathematical literacy skills and use of language that is by language standards that can be applied and well interpreted by the students. Based on the students' answers, it can be seen that the questions and activities are included in the practical category because they can be solved well by students. From the results, it can be concluded that the developed PISA-like numeracy and activity has a potential effect on mathematical literacy skills and life in the context of religious days during the pandemic. In addition, IBL model can improve students' communication skills in solving PISA-type math problems and activities.